Antibody responses of domestic animals to salivary antigens of Triatoma infestans as biomarkers for low-level infestation of triatomines - Schwarz, Alexandra (2009)
Hematophagous arthropods such as Triatoma infestans, the vector of Trypanosoma cruzi, elicit host-immune responses during feeding. Characterization of antibody responses to salivary antigens offers the potential to develop immunologically based monitoring techniques for exposure to re-emergent triatomine bug populations in peridomestic animals. IgG-antibody responses to the salivary antigens of T. infestans have been detected in chickens as soon as 2 days after the first exposure to five adult bugs. Chickens and guinea pigs regularly exposed to this number of triatomines showed a significantly lower anti-saliva antibody titre than animals exposed to 25 adults and fifth instars of four different T. infestans strains originating from Bolivia and from Northern Chile. Highly immunogenic salivary antigens of 14 and 21 kDa were recognised by all chicken sera and of 79 kDa by all guinea pig sera. Cross-reactivity studies using saliva or salivary gland extracts from different hematophagous species, e.g. different triatomines, bed bugs, mosquitoes, sand flies and ticks, as well as chicken sera exposed to triatomines and mosquitoes, demonstrated that the 14 and 21 kDa salivary antigens were only found in triatomines. Sera from peridomestic chickens and guinea pigs in sites of known T. infestans challenge in Bolivia also recognised the 14 and 21 kDa antigens. These represent promising epidemiological markers for the detection of small numbers of feeding bugs and hence may be a new tool for vector surveillance in Chagas disease control programs.